Impact of China’s environmental protection tax on green total factor productivity: based on the perspective of digital transformation - Zhang, Jie; Hua, Hongyan; Yang, Lianfen; Nie, Zhiping (Frontiers in Environmental Science, 2024)
Greening and digital transformation have become the new driving forces of China's economic development. The environmental protection tax (EPT) represents a significant economic measure for environmental protection in China, with the primary objective of safeguarding the environment.Using a 2012-2021 sample of Shanghai and Shenzhen A-share listed companies and the differencein-differences (DID) method, we empirically investigate the effect of the implementation of China's EPT on green total factor productivity (GTFP) of heavily polluting enterprises. The results show a significant increase in firms' GTFP after the implementation of the tax. A mechanism test reveals that firms' digital transformation has a masking effect, which inhibits the growth of firms' GTFP. Further analyses investigate the variations in effects based on ownership type, firm size, and market concentration. The positive effect is more pronounced for state-owned enterprises, large enterprises, and those operating in highly concentrated markets. This paper provides theoretical support and empirical evidence for the digital transformation and green development of heavily polluting enterprises, the rational optimization of EPT policies, and the promotion of sustainable economic development.